2019
DOI: 10.2494/photopolymer.32.373
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Bile Duct Stent Having Antifouling Properties Using Biomimetics Technique

Abstract: Biomimetics is a field of technologies based on imitating the functions and properties found in living organisms. The application of the super-water-repellent fine structure of lotus leaves to create waterproof products is a well-known example of biomimetics. The present study examined the surface structure of snail shells, which exhibit oleophobic properties oil repellency and explored the feasibility of recreating this structure on the inner surfaces of conventional biliary stents. Observations of snail shel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Ren et al have recently reported “mucus-like and hierarchical ciliary bionic” antifouling surfaces for marine antifouling applications [ 63 ]. Another group have used snail shells exhibiting oleophobic properties and a surface texture [ 64 ] to explore the feasibility of recreating similar structures on the inner surfaces of conventional biliary stents for antifouling purposes in medical fields [ 65 ]. Detailed electron microscopy observations of snail shells demonstrated surface features of around 200 nm in size.…”
Section: Biomimetic Antifouling Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Ren et al have recently reported “mucus-like and hierarchical ciliary bionic” antifouling surfaces for marine antifouling applications [ 63 ]. Another group have used snail shells exhibiting oleophobic properties and a surface texture [ 64 ] to explore the feasibility of recreating similar structures on the inner surfaces of conventional biliary stents for antifouling purposes in medical fields [ 65 ]. Detailed electron microscopy observations of snail shells demonstrated surface features of around 200 nm in size.…”
Section: Biomimetic Antifouling Strategiesmentioning
confidence: 99%
“…The authors hypothesized that when water enters the pores between these surface features, a film of water exhibiting super-nanohydrophilic structure forms on the shell, thus creating an oil-repellent surface with some antifouling effect. They were able to replicate analogous surface features on stents and conduct in vivo studies that demonstrated antifouling effects on the basis of a reduction in fouled surface area observed [ 65 ].…”
Section: Biomimetic Antifouling Strategiesmentioning
confidence: 99%
“…From theses backgrounds, we have been developing the antifouling technology [23][24][25][26][27][28][29] of the measurement target used by metamaterial effect. In this study, in preparation of the antifouling technology development, stick some kinds of sheets and evaluate the effect against to the water and the muddy water.…”
Section: Introductionmentioning
confidence: 99%
“…From theses backgrounds, we have been developing the antifouling technology of the measurement target used by metamaterial effect [5][6][7][8][9][10]. There have been many studies on polymer surfaces and water droplets [11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%